K.H. ABDURRAHMAN WAHID DAN PEMIKIRANNYA TENTANG HAKIKAT DAN TUJUAN PENDIDIKAN ISLAM - Hamida Olfah (Cross-border, 2020)
This paper analyzes the thoughts of K. H. Abdurrahman Wahid about the nature and purpose of Islamic education. K. H. Abdurrahman Wahid is the nation's teacher, reformer, scholar, thinker, and political leader. This can be seen in his works and his direct involvement in politics and education. His ideas contributed greatly to the world of Indonesian Islamic education. The method used in this study is library research, what is meant by literature research is a research activity carried out by collecting data in the form of books, papers, articles, magazines, journals, web (internet) and previous research results related to the ideas and thoughts of K. H. Abdurrahman Wahid in the field of Islamic education. The question to be answered in this paper is, how Gus Dur thinks about the nature and purpose of Islamic education. The result of this study is, The concept of education that Gus Dur wants to develop is religious multiculturalism based education, which is an educational concept based on religious beliefs and aims to guide or deliver students to become complete human beings, independent and free from the shackles of oppression. In this concept, he does not seem to reject the potential for otherness to be further acted upon in a clear concept by placing heterogeneity as an integral part of education itself. Gus Dur has offered several concepts regarding the purpose of Islamic education: Islamic education based on modernism, Islamic education based on liberation, and Islamic education based on diversity (multiculturalism).